ОЦІНКА ВПЛИВУ СТРУКТУРНИХ ЗМІН В ЦЕНТРАЛІЗОВАНОМУ ТЕПЛОПОСТАЧАННІ УКРАЇНИ НА ОБСЯГИ ВИКИДІВ ПАРНИКОВИХ ГАЗІВ - DERII, V.; NECHAIEVA, T.; LESHCHENKO, I. (PH “Akademperiodyka”, 2023)
Introduction. The energy sector makes the largest contribution of about 65% of the total amount to greenhouse gas (GHG) emissions in Ukraine. District heating systems (DHS) as an energy subsector are a significant source of GHG emissions as a result of the combustion of fossil carbon fuels (natural gas, coal, petroleum products, peat, etc.).Problem Statement. Due to its obvious advantages, DHS will continue to develop with the use of advanced te chnologies that allow a significant increase in the efficiency and a reduction in heat losses, and accordingly ensure the lowest cost of heat energy for consumers. However, at the moment, no forecast has been made for the dyna mics of Ukraine’s DHS fuel balance, the heat generation structure, and, accordingly, GHG emissions until 2050.Purpose. The purpose of this research is to estimate the impact of structural changes in the DHS on the greenhouse gas emissions.Material and Methods. Publications in scholarly research journals, official documents, statistical data, methods of statistical and comparative analysis have been used. Calculations have been made with the use of the Methodology of the United Nations Intergovernmental Panel on Climate Change (UN IPCC).Results. Changes in the fuel balance and the generation structure of DHS of Ukraine have been forecasted. According to the forecast results, the natural gas consumption will decrease 1.4—2 times, while that of coal will fall 1.4—5.9 times. Petroleum products will not be used in DHS after 2040, but the electricity consumption will increase 7.7—19 times. At the same time, the biomass consumption will increase 2 times, and that of solar energy will grow 77 times, as compared with 2020. In 2050, the GHG emissions from DHS will amount to 3.9—6.9 million tons of CO2-eq., depending on the DHS structural dynamics scenario.Conclusions. The forecast of the structure of Ukraine’s DHS heat energy generation has predicted a 4.4 times reduction in the greenhouse gas emissions by 2050 for the optimistic and 2.5 times reduction for the pessimistic scenario of the DHS development, as compared with 2020.